Major substructure in the M31 outer halo: the east cloud - McMonigal, Brendan; Huxor, Avon P. (Arxiv, 2015)
We present the first detailed analysis of the East Cloud, a highly disrupted diffuse stellar substructure in the outer halo of M31. The core of the substructure lies at a projected distance of $\sim100$ kpc from the centre of M31 in the outer halo, with possible extensions reaching right into the inner halo. Using Pan-Andromeda Archaeological Survey photometry of red giant branch stars, we measure the distance, metallicity and brightness of the cloud. Using Hubble Space Telescope data, we independently measure the distance and metallicity to the two globular clusters coincident with the East Cloud core, PA-57 and PA-58, and find their distances to be consistent with the cloud. Four further globular clusters coincident with the substructure extensions are identified as potentially associated. Combining the analyses, we determine a distance to the cloud of $814^{+20}_{-9}$ kpc, a metallicity of $[Fe/H] = -1.2±0.1$, and a brightness of $M_V = -10.7±0.4$ mag. Even allowing for the inclusion of the potential extensions, this accounts for less than $20$ per cent of the progenitor luminosity implied by the luminosity-metallicity relation. Using the updated techniques developed for this analysis, we also refine our estimates of the distance and brightness of the South-West Cloud, a separate substructure analyzed in the previous work in this series.